DIVERSITY AND CORRELATION OF BODY CIRCLE DIMENSIONS OF BALI CATTLE AT PUSAT PEMBIBITAN SAPI BALI UNGGUL GEROKGAK, BULELENG, BALI - Anindya, Ainaya Luthfi; Sampurna, I Putu; Susari, Ni Nyoman Werdi (Buletin Veteriner Udayana, 2023)
Bali cattle are one of the native Indonesian cattle that have great potential as a meat producer. The potential population of Bali cattle in Gerokgak, with existing supporting facilities, is the reason for the importance of continuous selection so that the genetic quality of individuals can be improved, selection can be done through measurement (quantitative). This study aims to determine the diversity and correlation between circumference dimensions of bali cattle based on body circumference measurements of bali cows. This study used a purposive sampling method on 25 adult bali cattle kept at the Bali Superior Cattle Breeding Center in Gerogak, Buleleng, Bali. Then the data was processed by descriptive analysis and biplot analysis using the SPSS version 26. The results obtained were in the form of the smallest (uniform) coefficient of diversity for bali cattle is chest circumference of 5,13%, followed by upper neck circumference of 6,38%, the steering circumference is 7,74% and the most diverse is the lower neck circumference of 8,69%. Chest circumference is positively correlated with lower neck circumference and upper neck circumference but negatively correlated with steering circumference. It is recommended to make a selection on the steering wheel of the cow and pay attention to the management of the maintenance of Bali cattle because these two things are interconnected in producing superior breeds of cows.